2022
DOI: 10.3390/cancers14061383
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Tumor Infiltrating Lymphocytes in Adenoid Cystic Carcinoma of the Head and Neck

Abstract: Adenoid cystic carcinoma (ACC) is a rare malignancy in the head and neck. The prognosis remains poor and late recurrences often occur after 5 years and later. To date, there are no reliable prognostic markers for ACC. In several solid tumors, tertiary lymphoid structures (TLS) are associated with improved survival. This study aims to investigate the role of distribution patterns of tumor infiltrating immune cells (TIL) in ACC. A cohort of 50 patients from three different cancer centers was available for analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
3
10
0
Order By: Relevance
“…Our data are consistent with those of previous studies that showed that ACC is a cancer with low immunogenicity, using immunohistochemistry 21–23 . It has been reported that immune checkpoint inhibitors are not effective in ACC, which may be in part a result of low immunogenicity 24,25 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our data are consistent with those of previous studies that showed that ACC is a cancer with low immunogenicity, using immunohistochemistry 21–23 . It has been reported that immune checkpoint inhibitors are not effective in ACC, which may be in part a result of low immunogenicity 24,25 .…”
Section: Discussionsupporting
confidence: 92%
“…The level of TIL expression is not suitable as a predictive biomarker for immunotherapy in ACC, possibly due to a similar cause 22 . In a previous study analyzing TIL patterns in ACC, it was reported that the IP, represented by the spatial distribution of TIL, has no clear association with clinical outcomes 23 . Our analysis found that the IP in ACC was not associated with PFS with axitinib use.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…It is considered an immunologically cold tumor characterized by a low tumor mutation burden, low expression of tumor antigens, and a microenvironment with limited immunity. [6][7][8][9] The details of the immunological processes underlying this phenomenon need further investigation.…”
Section: Introductionmentioning
confidence: 99%